Systematic review of caregiver burden in spouses and partners providing informal care to wounded, injured or sick (WIS) military personnel. Issue 5 (12th February 2018) - Thandi, Gursimran; Harden, L; Cole, L; Greenberg, N; Fear, N T
Abstract : Introduction: For the purposes of this review, caregivers are individuals who provide care that is typically unpaid and usually takes place at home. This systematic review aims to identify burden among spouses/partners caring for wounded, injured or sick military personnel and the factors associated with caregiver burden. Methods: A systematic review was undertaken using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses reporting guidelines. Five electronic databases and relevant websites were searched. Two reviewers appraised the quality of the studies and carried out data extraction. Results: Ten original papers were identified, of which eight were quantitative studies and two were qualitative. These papers highlighted the potential negative impact caregiving can have on spouses/partners and also some of the positive aspects of caring that can strengthen intimate relationships. Conclusions: Caring for an injured or ill military spouse or partner is a difficult task, compounded by the complexity of dealing with potentially both their physical and mental health problems. However, research has also identified some positive aspects of caring that can strengthen intimate relationships.